rs401502 and rs11575934 Polymorphisms of the IL-12 Receptor Beta 1 Gene are Protective Against Colorectal Carcinogenesis - Jelassi, Refka; Dhouioui, Sabrine; Ben Salah, Hamza; Saidi, Nasreddine; Mzoughi, Nabiha; Ammi, Radhia; Bouratbine, Aida; Aoun, Karim; Zidi, Ines; Chelbi, Hanen (Frontiers in Genetics, 2022)
Background: Colorectal cancer (CRC) is a major public health problem worldwide and in Tunisia. It ranks among the first cancers in terms of incidence and cancer-related cause of death rates. Its pathogenesis is currently considered to be multifactorial involving genetic and environmental factors. Studies have suggested that IL-12RB1 may be involved in the susceptibility to inherited CRC. Hence, the interest of studying the role of single nucleotide polymorphisms (SNPs) within the IL-12RB1 gene (rs401502 and rs11575934) in susceptibility to CRC. Aim: Our purpose was to assess whether genetic variants IL-12RB1 +1196G/C (rs401502) and IL-12RB1 +705A/G (rs11575934) within IL-12RB1 gene are associated with the CRC risk. Method: A total of 110 Tunisian patients with CRC and 141 healthy control subjects were included in this study. Genotyping was performed by High-Resolution Melting (HRM) analysis. All results were confirmed by direct DNA sequencing or PCR-RFLP methods. Later, the allele frequencies and genotype distribution were established and compared between control group and CRC patients. Results: Our results shows that the mutant allele frequencies of rs401502 and rs11575934 SNPs were 24% and 30% respectively, in control group and 16%, 21% respectively among patients. In addition, the two SNP were in Hardy Weinberg Equilibrium (HWE) in both patients and controls. Association study showed a significant association of the two polymorphisms with CRC, according to the dominant genetic model (p=0.03 and 0.02, respectively). Conclusion: Our study shows a potential protective effect of the two studied IL-12RB1 gene polymorphisms (rs401502 and rs11575934) in CRC.